A two-arm, randomized, controlled, multi-centric, open-label phase-2 study to evaluate the efficacy and safety of Itolizumab in moderate to severe ARDS patients due to COVID-19. (4th May 2021) - Kumar, Suresh; De Souza, Rosemarie; Nadkar, Milind; Guleria, Randeep; Trikha, Anjan; Joshi, Shashank R.; Loganathan, Subramanian; Vaidyanathan, Sivakumar; Marwah, Ashwani; Athalye, Sandeep N.
ABSTRACT: Objective : Efficacy and safety of Itolizumab, an immunomodulatory mAb, in treating moderate-to-severe acute respiratory distress syndrome (ARDS) due to cytokine release in COVID-19 patients was evaluated in a multi-centric, open-label, two-arm, controlled, randomized, phase-2 study. Methods : Patients were randomized (2:1) to Arm-A (best supportive care [BSC]+Itolizumab) and Arm-B (BSC). Primary outcome of interest was reduction in mortality 30-days after enrollment. Results : Thirty-six patients were screened, five treated as first-dose-sentinels and rest randomized, while four patients were screen-failures. Two patients in Arm-A discontinued prior to receiving one complete infusion and were replaced. At end of 1-month, there were three deaths in Arm-B, and none in Arm-A (p = 0.0296; 95% CI = −0.3 [−0.61, −0.08]). At end of study, more patients in Arm-A had improved SpO2 without increasing FiO2 (p = 0.0296), improved PaO2 (p = 0.0296), and reduction in IL-6 (43 vs 212 pg/ml; p = 0.0296) and tumor necrotic factor-α (9 vs 39 pg/ml; p = 0.0253) levels. Transient lymphopenia (Arm-A: 11 patients) and infusion reactions (7 patients) were commonly reported treatment-related safety events. Conclusion : Itolizumab is a promising, safe and effective immunomodulatory therapy for treatment of ARDS due to cytokine release in COVID-19 patients, with survival and recovery-benefit.